Exploration and Practice of Course Ideological and Political Education in Clinical Skills Training Courses - Du, Yaming (International Journal of Global Economics and Management, 2024)
The effective integration of ideological and political education with medical professional courses is one of the most important contents of medical teaching reform. It is a process of organic unity of knowledge transmission and value guidance, and is the key to the implementation of the Healthy China strategy and the "moral education". This study analyzes the necessity of carrying out ideological and political education in clinical skills training courses, and combines the characteristics of clinical skills training courses to integrate ideological and political education from the aspects of revising experimental teaching objectives, optimizing experimental teaching content, innovating practical training teaching methods, and improving experimental evaluation mechanisms. The aim is to carry out ideological and political education with professional knowledge, achieve the subtle integration of ideological and political education into the brain and heart, and guide medical students to establish a correct outlook on life Values, cultivate students’ patriotism, national confidence, and professional spirit of respecting life, advocating medical ethics, selfless dedication, and overcoming obstacles, so that students can learn and apply what they have learned.